PENERAPAN ANALISIS BERBASIS OBJEK PADA SISTEM INFORMASI AKADEMIK PROGRAM STUDI TEKNIK TELEKOMUNIKASI DAN JARINGAN TELEKOMUNIKASI DIGITAL - Mas’udia, Putri Elfa; Sarosa, Moechammad; Astami, Tridon Yang; Atmaja, Wahyu Bambang Try (DINAMIKA DOTCOM, 2015)
The academic data at Telecomunication Enginering Study Program of State Polytechnic of Malang is manually processed. Manual data processing has some weakness. It will take a longer time to process the data, and it will also increase the potential of data redundance and human error. So that, it is needed to develop a computerized academic information system, that is integrated to a database management system and is accessible internet. Academic information system of Telecomunication Engineering study program is aimed to process lecturers, students, courses and other academic data and to make it accessible through internet. The requirement analysis and software design is done by using Object Oriented method. And Object Oriented Modeling is used to visualize the software model.Â Some of modeling diagram that is used are Use Case diagram, Class diagram, Activity diagram and Sequence diagram. Then the software is developed based on the result of analysis and design. The implemented system has been tested and could be used to manage lecturers, courses, students, lecturing, GBPP, SAP, course contract and grading.Â Kata Kunci :academic information system, web, object oriented analysis